2019
DOI: 10.1017/s0144686x1800171x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term care preference among Japanese older adults: differences by age, period and cohort

Abstract: This study examined the differences in the preference for long-term care (LTC) by age, period and cohort (A-P-C) in Japanese older adults through repeated cross-sectional surveys from 1998 – before the establishment of LTC insurance – to 2016, in a suburban city of metropolitan Tokyo. We analysed the direct effects of A-P-C on the preference for LTC, as well as the interaction effects of A-P-C on preference by gender, family structure and activities of daily living. Data were obtained at six time-points using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 47 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…Before the implementation of the long-term care insurance system, 43% of older patients stayed in hospitals for more than six months due to the lack of long-term care facilities [28], but the provisions of formal care, including long-term care facilities and home care services, have been enriched in both quantity and quality since then. Indeed, according to a recent study of Japanese older adults [29], the preference for home care services increased before and after the reinforcement of the long-term care insurance system, but the preference for long-term care services remained relatively stable. Therefore, our findings should be updated to reflect more recent data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Before the implementation of the long-term care insurance system, 43% of older patients stayed in hospitals for more than six months due to the lack of long-term care facilities [28], but the provisions of formal care, including long-term care facilities and home care services, have been enriched in both quantity and quality since then. Indeed, according to a recent study of Japanese older adults [29], the preference for home care services increased before and after the reinforcement of the long-term care insurance system, but the preference for long-term care services remained relatively stable. Therefore, our findings should be updated to reflect more recent data.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we need to be careful in generalizing the present results and interpreting differences across studies. For instance, another study of Japanese older adults [29] reported that the ratio of respondents preferring to reside in longterm care facilities if confined to bed was 30.1% in 1998. Unlike the present study, however, the measurement did not include a hospital as a long-term care facility.…”
Section: Discussionmentioning
confidence: 99%
“… 15 - 17 ) Several studies have reported that individuals who live alone, women, and younger people prefer institutional care. 13 , 18 ) In contrast, men generally prefer informal care. 13 , 18 , 19 ) Studies have also shown a positive relationship between individuals' education level and their preferences for institutional (or formal) care.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty‐nine studies out of 35 studies explored the impact of age on willingness of older people to engage with long‐term care services in 110,119 participants. Fifteen studies found a significant association between age and the willingness of older people to engage with long‐term care services (Carvalho et al, 2020; Hajek et al, 2017; Han et al, 2017; Kim & Kim, 2004; Liao, 2019; McCormick et al, 2002; Qian et al, 2018; Rodríguez, 2014; Shi & Hu, 2020; Sugisawa et al, 2020; Wang et al, 2004, 2020; Wei & Zhang, 2020; Xu et al, 2018; Zeng et al, 2019). And 10 studies found that the younger older people were likely to choose formal care.…”
Section: Resultsmentioning
confidence: 99%